Black women in white : racial conflict and cooperation in the nursing profession, 1890-1950 - Hine, Darlene Clark (Indiana University Press, 1989)
This pathbreaking study analyzes the impact of racism on the development of the nursing profession, particularly on black women in the profession.
Keywords: Umschulungswerkstätten für Siedler und Auswanderer -- Bitterfeld; African American nurses -- History.; Nursing -- United States -- History.; United States -- Race relations -- History.; Black or African American -- history; History of Nursing; Race Relations -- history; United States; Infirmières noires américaines -- Histoire.; États-Unis -- Relations raciales -- Histoire.; MEDICAL -- Nursing -- Issues.; African American nurses; Nursing; Race relations; Schwarze; Rassenkonflikt; Krankenpflege; Schwärze; USA; Verpleegkundigen.; Rassenvraagstuk.; Geschichte (1890-1950); African American nurses -- History; Geschichte -- 1890-1950; Nursing -- History -- United States; United States -- Race relations -- History; History